Performance measurement of the after-sales service network: Evidence from the automotive industry - Shahnoush Shahrouzi Fard; Seyed Mehdi Hosseini (Management Science Letters)
This paper presents an empirical investigation to determine important factors influencing on customer satisfaction in after-sales service network of automotive industry. The study designs two questionnaires, one for measuring the quality of after-sales services and the other for measuring customers’ satisfaction. The study selects a sample of 265 randomly selected customers out of 850 people who received the services from an automotive firm in Iran. Cronbach alpha has calculated as 0.82, which is well above the minimum desirable level. Using Spearman correlation the study has detected a positive and meaningful relationship between services and customer satisfaction (r=0.48, Sig. =0.01), a positive relationship between being responsiveness and customer satisfaction (r=0.51, Sig. =0.01) and finally a positive relationship between speed of operation customer satisfaction (r=0.45, Sig. = 0.01). Moreover, there was a positive and meaningful relationship between cost of services and customer satisfaction (r=0.68, Sig. = 0.01) and a positive relationship between quality of services of after-sales services and customer satisfaction (r = 0.61, Sig. =0.01).